Fenomena Tunakarya Terdidik Era 4.0 Di Kabupaten Tangerang (Studi Kasus di Kecamatan Sepatan) - Prakoso, Agung; Kudus, Wahid Abdul; Tesniyadi, Dema (EDU SOCIATA ( JURNAL PENDIDIKAN SOSIOLOGI ), 2024)
This study describes the phenomenon of educated unemployment in the 4.0 era. The background of this research is that the number of current unemployed so becomes a phenomena, whereas today has entered the era of 4.0. The type of research used is qualitative research with descriptive methods. The data collection techniques used in this research are observations, interviews, and documentation. The informants involved are the unemployed who are graduates of high school (SMA) and university graduates. The results of this study showed that educated unemployment occurred a lot in the district of Tangerang especially in the Sepatan district so it became a phenomenon. This is due to the inadequate qualifications required, the lack of quality education in preparing human resources to compete in the world of work, the minimal training of specialized skills to support the job, the administrative requirements of the job application are too complex, and the mastery of technology is still minimal. In this study, using the theory of education and division of labour that education is one of the factors of the phenomenon of educated unemployment to the occurrence of division of work in the era 4.0.